Analytical method development for polyphenol detection in rat plasma using green tea-loaded chitosan-iron oxide nanoparticles - Al Awawdeh, Safaa; Shafie, Nurul Husna; Ishak, Amirah Haziyah; Mohd Esa, Norhaizan; Loh, Su Peng; Nurdin, Armania (Springer, 2025)
Green tea polyphenols (GTPP) are recognized for their significant biological activities. However, despite extensive research, the plasma concentrations of key GTPP remain insufficiently characterized, primarily due to their inherent instability, extensive biotransformation and rapid metabolism, all of which significantly affect their bioavailability. In this research, a reliable and optimized high performance liquid chromatography (HPLC) method was established for quantitative determination of six key GTPP: catechin, gallic acid, epicatechin, epigallocatechin gallate (EGCG), caffeine and theaflavin. The method was effectively adapted in order to analysis of these compounds encapsulated in iron oxide chitosan nanoparticles (GTPP-IOCHNP) in rat plasma. Using a C18 column, chromatographic separation was accomplished using a programmed gradient elution with mobile phase made up of (A) an aqueous solution of 0.1% formic acid and (B) acetonitrile containing 0.1% formic acid, at flow rate of 1.0 mL/min and wavelength of 280 nm. All analytes demonstrated good linearity with correlation coefficients (R²) ≥ 0.992 in both reference standards and plasma spiked samples, with back calculated concentrations within ± 15% of the nominal values. Limits of quantification (LOQs) ranged between 0.964 and 5.663 µg/mL for standard solutions and between 1.783 and 9.542 µg/mL for plasma spiked samples. Extraction recoveries for gallic acid, catechin, caffeine, EGCG, and theaflavin were 73.2 ± 0.16%, 63.9 ± 0.17%, 99.9 ± 0.03%, 79.9 ± 0.025%, and 91.4 ± 0.17%, respectively, with relative standard deviations (RSD%) within ± 15%. This validated method demonstrated rapid, sensitive and precise and was effectively applied to quantify GTPP in rat plasma after oral administration of GTPP-IOCHNP.